PENGARUH LINGKUNGAN BISNIS TERHADAP USAHA KECIL DAN MENENGAH DI JAWA TIMUR - Lukman Lukman (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2012)
This research aims to analyze: indicators that can be explained in a timely and consistent in measuring environmental business area, invalid constructs influences and contributions to the business environment of SMES, good size variansi is not made directly to it. The Data used in this research is data cross section of the County/city in East Java on priode in 2010, which is sourced from the secondary data KPPOD and BPPS. An analysis using Structural Equation Model approach. With the method of least square estimation of weight (WLS) and processed with LISREL program Student. Research results show that the area of business environment indicators precise and consistent in explaining the business environment is kostruk security and resulusi conflicts, transaction costs in the area, access to land and business assurance efforts, licensing business, the management of infrastructure in the area, local government interactions with businessmen.DOI: 10.15408/sjie.v1i1.2597